Representasi Unsur-Unsur Budaya Lokal Gorontalo pada Seni Mural - Apris K. Toheto; I Wayan Sudana; Hasmah Lagau (Universitas Sultan Ageng Tirtayasa, 2026)
The existence of mural art in Gorontalo not only functions as an aesthetic expression, but also as a medium for representing local cultural elements. However, the cultural elements represented in the murals have not been comprehensively revealed. This study aims to reveal the representation of Gorontalo culture in mural art based on Koentjaraningrat's theory of seven cultural elements. The study uses a qualitative case study model method. Data were collected through observation, interviews and literature studies, then analyzed through data reduction, data display, and drawing conclusions. The results show that mural art in Gorontalo represents local culture according to the theory of seven cultural elements. The language system is represented by a mural entitled Hulonthalo Lipu'u. The knowledge system is represented by a mural entitled the life of the Gorontalo people. The social organization system is represented by a mural entitled Gorontalo traditional clothing. The system of living equipment and technology is represented in murals entitled nature and culture, Gorontalo culture murals, and Gorontalo community life murals. The economic system of livelihood is represented by murals entitled nature and culture and murals of Gorontalo community life. Religious systems are represented in murals titled